PENGARUH PIJAT SAKRAL TERHADAP INTENSITAS NYERI PADA PERSALINAN KALA I : EVIDENCE BASED CASE REPORT (EBCR) (Jurnal Kesehatan Siliwangi, 2022)
Background: Childbirth is a physiological event in a woman's life. One of the most excruciating pains a mother has ever gone through is childbirth pain. The pain that mothers feel during labor is caused by pain signals that are sent as the uterine muscles contract, pushing the baby to the outside of the uterus. How to deal with labor pain can be done by pharmacological and non-pharmacological. One way of non-pharmacological management to reduce labor pain is sacral massage. Purpose: This EBCR aims to determine the effect of sacral massage on pain intensity in the first stage of labor. Method: The method used in writing the EBCR is by searching for evidence through databases from Pubmed and Google Scholar with the years published 2015-2021. Result: Giving sacral massage 6-8 times carried out by birth attendants for 20 minutes during the first stage of labor and it is proven that the mother feels more relaxed and comfortable and the pain is reduced after being given sacral massage therapy. Conclusion: Sacral massage is an effective way to reduce pain in the first stage of labor.